2003
DOI: 10.2166/wst.2003.0411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural and modified zeolite addition on anaerobic digestion of piggery waste

Abstract: The effect of natural and modified zeolites on the anaerobic degradation of acetate and methanol was evaluated by the determination of specific methane productivity (SMP) in batch minidigesters of 50 mL at doses of 0.01, 0.05 and 0.1 g of zeolite/g of VSS. The effects of the different zeolite concentrations were determined by the results of the SMP. A kinetic characterization with data of accumulated methane gas volume was also carried out. In the second phase of the study, the effects of natural and nickel ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 16 publications
1
29
0
1
Order By: Relevance
“…Since zeolite R1 had the smallest diameter compared with zeolite R2 and R3, therefore increasing the surface area of zeolite for attachment and colonization of SRB. These enhancements influenced microbial and enzymatic transformation of a variety of substances for sulphate reducing bacterial during their attachment and colonization in the zeolite surface [26][27][28]. In addition zeolites have been reported to absorb manganese and other heavy metals [29][30].…”
Section: Effect Of Different Diameter Size Of Natural Zeolite On Mixementioning
confidence: 99%
“…Since zeolite R1 had the smallest diameter compared with zeolite R2 and R3, therefore increasing the surface area of zeolite for attachment and colonization of SRB. These enhancements influenced microbial and enzymatic transformation of a variety of substances for sulphate reducing bacterial during their attachment and colonization in the zeolite surface [26][27][28]. In addition zeolites have been reported to absorb manganese and other heavy metals [29][30].…”
Section: Effect Of Different Diameter Size Of Natural Zeolite On Mixementioning
confidence: 99%
“…However, conventional digesters used in rural areas must be operated at retention times higher than 20 days in order to achieve adequate organic matter removal efficiencies and prevent the washout of microorganisms. The increase of wastewater anaerobic process efficiency by using natural and modified zeolites has been pointed out by several authors [5,6]. The adequate doses of natural zeolite have also been studied [7].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nickel in anaerobic digestion processes could increase acetate utilization rate of methanogenic bacteria. Similarly, Milán et al [9] observed the modified zeolite with nickel increase the methanogenic specific activity by 2.8 times in anaerobic digestion of piggery waste. Nickel was a unique micronutrient for methanogenic bacteria.…”
Section: Discussionmentioning
confidence: 79%